A fundamentalidade do direito à água : uma análise a partir da justiça social e dos Objetivos do Desenvolvimento Sustentável - Santos, Raquel Magali Pretto dos (2025)
This dissertation addresses the fundamental nature of the right to water, analyzing it as an inseparable element of human dignity and an imperative of social justice. The research question focuses on the gap between the normative recognition of the right to water and its practical implementation in Brazil, which, despite abundant water, faces profound inequality in access. The overall objective is, therefore, to analyze the fundamental nature of the right to water from the perspective of social justice and the Sustainable Development Goals (SDGs), with a focus on SDG 6. The central hypothesis is that the national water crisis is not a physical scarcity, but rather a crisis of management, planning, and justice, the overcoming of which depends on the recognition of the right to water as an autonomous fundamental right. To this end, a theoretical-hipothetical- deductive approach was employed, with bibliographical and documentary research. The work is part of the Area of Concentration: New Paradigms of Law and the Research Line: Social Relations and Dimensions of Power, of the Stricto Sensu Postgraduate Program in Law at the University of Passo Fundo. The analysis is grounded in theories of justice and national and international normative frameworks. It is concluded that realizing the right to water as a pillar for development and democracy requires proactive state action, the strengthening of participatory governance, and social mobilization, transforming water into a vector of citizenship and development for all, in line with the principles of the 2030 Agenda.